Ta có:
[TEX]\frac{a}{x}+\frac{b}{y}+\frac{c}{z}=0[/TEX]
[TEX]\Leftrightarrow \frac{axy}{xyz}+\frac{bxz}{xyz}+\frac{cxy}{xyz}=0[/TEX]
[TEX]\Leftrightarrow \frac{axy+bxz+cxy}{xyz}=0[/TEX]
[TEX]\Leftrightarrow axy+bxz+cxy=0[/TEX] (1)
Ta có:
[TEX]\Leftrightarrow \frac{x}{a}+\frac{y}{b}+\frac{z}{c}=1[/TEX]
[TEX]\Leftrightarrow{\left( \frac{x}{a}+\frac{y}{b}+\frac{z}{c}\right)}^{2}=1[/TEX]
[TEX]\Leftrightarrow {\left( \frac{x}{a}\right)}^{2}+{\left( \frac{y}{b}\right)}^{2}+{\left( \frac{z}{c}\right)}^{2}+2.\frac{xy}{ab}+2.\frac{yz}{bc}+2.\frac{xz}{ac}=1[/TEX]
[TEX]\Leftrightarrow {\left( \frac{x}{a}\right)}^{2}+{\left( \frac{y}{b}\right)}^{2}+{\left( \frac{z}{c}\right)}^{2}+2\left( \frac{xy}{ab}+\frac{yz}{bc}+\frac{xz}{ac}\right)=1[/TEX]
[TEX]\Leftrightarrow {\left( \frac{x}{a}\right)}^{2}+{\left( \frac{y}{b}\right)}^{2}+{\left( \frac{z}{c}\right)}^{2}+2\left( \frac{cxy}{abc}+\frac{ayz}{abc}+\frac{bxz}{abc}\right)=1[/TEX] (2)
Thế (1) vào (2), ta có:
[TEX]\Leftrightarrow {\left( \frac{x}{a}\right)}^{2}+{\left( \frac{y}{b}\right)}^{2}+{\left( \frac{z}{c}\right)}^{2}=1[/SIZE][/FONT][/TEX]